Northwestern Anagram Test-Italian (Nat-I) for primary progressive aphasia. (October 2019) - Canu, Elisa; Agosta, Federica; Imperiale, Francesca; Ferraro, Pilar M.; Fontana, Andrea; Magnani, Giuseppe; Mesulam, Marek-Marsel; Thompson, Cynthia K.; Weintraub, Sandra; Moro, Andrea; Cappa, Stefano F.; Filippi, Massimo
Abstract: Objectives: To test the ability of the Northwestern Anagram Test-Italian (NAT-I) to distinguish between the non-fluent/agrammatic (nfv-) and phonological/logopenic (lv-) variants of primary progressive aphasia (PPA), and to determine the relationship between NAT-I variables and brain integrity in PPA patients. Methods: 13 nfvPPA and 8 lvPPA patients underwent the 44-item-version of NAT-I and brain MRI. The NAT-I was also administered to six patients with the semantic variant (sv) PPA to sample performance in cases with no grammatical deficits. Performances were recorded and compared between patient groups. Receiver Operating Characteristic curve analysis assessed the ability of NAT-I to discriminate nfvPPA and lvPPA. The correlation between anatomical changes and NAT-I variables were assessed. A shortened (22-item)-version of NAT-I was also tested for classification ability. Results: Participants with NfvPPA performed more poorly than lvPPA patients on canonical and non-canonical sentences. NAT-I non-canonical sentence and total scores achieved the highest diagnostic accuracy in discriminating the two patient groups (area under the curve: .93 and .91, respectively). SvPPA participants showed performances similar to lvPPA. NAT-I variables correlated with the integrity of the left inferior frontal gyrus and the body of the corpus callosum. The NAT-I 22-item-version total and non-canonical sentences scores reached diagnostic accuracy comparable to the full version. Conclusions: The NAT-I, in particular the measure of non-canonical syntax, is an effective tool for distinguishing nfvPPA and lvPPA patients and correlated with the integrity of crucial brain regions implicated in syntactic processing. The 22-item-brief version of NAT-I is suitable for clinical practice and research.